Extracorporeal life support in pediatric burn care: A systematic review. Issue 3 (March 2023) - Maybauer, Marc O; Maybauer, Dirk M; Capoccia, Massimo
A systematic review of the role of extracorporeal life support (ECLS) in pediatric patients with burn and smoke inhalation injury was undertaken. A systematic search of the literature according to a specific combination of keywords to ascertain the effectiveness of this treatment strategy was conducted. A total of 14 articles out of 266 were considered suitable for the analysis in pediatric patients. The PICOS approach and PRISMA flow chart were followed for the purpose of this review. Despite the limited number of studies on the subject, ECMO in burn and smoke inhalation injury provides an additional level of support in pediatric patients leading to positive outcomes. V-V ECMO demonstrated the best overall survival of all configurations, with similar outcomes to non-burned patients. Prolonged mechanical ventilation prior to ECMO decreases survival and increases mortality by 12% with each additional day off ECMO. Good outcomes have been described for scald burns, dressing changes, and pre-ECMO cardiac arrest.